(3efJNH cJGH GdZGabi aj GdCOhjI GdeaQOIs - (3LeGd GdOjf ZQjZhQjS Hf gGQhf GdedWi GdSQjGfi GHf GdYHQis; (3GdZGabjs
(3ChdgG (B:s
(3HYO GdebOeI bGd ZQjZhQjhS GdaQjGf hdPdc LYdJ ZQV ef gPG GbJUGQi Ydi PcQ UaGJ GdCOhjI hGNJjGQgG hGdeTghQ abW ef CSeGFgG hbhGgG s
(3BNQgG (B:s
(3hgh CHjV ajg NThfI jSjQI hjbY ai eQGge GdQCS hZeQI GdhLg , hEf GdJi ai GdCMSGA faY ef faK GdOe s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B253 s
Keywords: (3GdWHs